Vietnamese Ginseng (Panax vietnamensis Ha and Grushv.): Phylogenetic, Phytochemical, and Pharmacological Profiles - Nguyen, Tung Huu; Phuong, Thuong Thien (Pharmacognosy Reviews)
Vietnamese ginseng(VG)(Panax vietnamensis, Araliaceae) is indigenous in the central high lands of Vietnam and the southernmost distribution in the Panax genus. Compared to the long history of use and overall research on Korean ginseng and American ginseng, the up-to-date publication on VG is relatively much less extensive. The studies on VG have been reported focusing on phylogenetic analysis, phytochemistry, and pharmacological activity. To date, there is no systematic review of VG. In this review, the phytochemical profile including 52 individual saponins of VG is described, it becomes noteworthy that ocotillol-type ginsenosides including majonoside R1 and majonoside R2 are unique and dominate in the title plant of the Panax spp. In addition, various pharmacological activities of VG extracts and components are summarized and discussed.
Keywords: Araliaceae; ginseng; ginsenoside; majonoside R2; Panax vietnamensis; Vietnamese ginseng